Ambient PM2.5 chronic exposure leads to cognitive decline in mice: From pulmonary to neuronal inflammation. (1st October 2020) - Shou, Yikai; Zhu, Xiaozheng; Zhu, Danna; Yin, Hongping; Shi, Yingying; Chen, Minyan; Lu, Linjie; Qian, Qiwei; Zhao, Dongjiu; Hu, Yu; Wang, Huanhuan
Highlights: Chronic exposure to ambient PM2.5 resulted in a significant reduction of cognitive ability in mice. Neuroinflammatory reaction induced by PM2.5 exposure occurred later than cognitive impairment in mice. The expression levels of integrity tight junction proteins in the blood-brain barrier were reduced by PM2.5 exposure. Abstract: Fine particulate matter 2.5 (PM2.5 ), one of the main components of air pollutants, seriously threatens human health. Possible neuronal dysfunction induced by PM2.5 has received extensive attention. However, there is little evidence for the specific biochemical mechanism of neuronal injury induced by PM2.5 . Moreover, the pathway for PM2.5 transport from peripheral circulation to the central nervous system (CNS) is still unclear. In the current work, C57BL/6 mice were chronically exposed to ambient PM2.5 for 3, 6, 9, and 12 months. Exposure to ambient PM2.5 resulted in a significant reduction of cognitive ability in mice by Morris water maze test. PM2.5 exposure induced a neuroinflammatory reaction after cognitive impairment, while inflammation in the hypothalamus and olfactory bulb tissue occurred earlier. The expression levels of integrity tight junction proteins in the blood-brain barrier (BBB) were reduced by PM2.5 exposure. Pulmonary inflammation occurred much earlier and diminished at later stage of PM2.5 exposure. The results indicated that chronic exposure to ambient PM2.5 led to cognitive decline in mice; CNS dysfunction may be due to neuroinflammatory reactions; the reduced integrity of the BBB allowed the influence of pulmonary inflammation to neuronal alterations. The work may provide promising therapeutic or preventive targets for air pollution-induced neurodegenerative disease.